Genome-wide identification of mildew resistance locus O (MLO) genes in tree model poplar (Populus trichocarpa): powdery mildew management in woody plants - (:unkn) unknown (SPRINGER, 2018)
Poplars are economically important fast growing trees. They are exposed to broad range of fungal diseases like powdery mildew (PM). MLOs (mildew resistance locus O), as plant susceptibility genes, act as negative regulators and whose loss-of-functions confer complete resistance to PM disease. Herein, work identified the MLO gene family members in poplar, a woody model species. A total of 26 identified MLOs (annotated as PtMLO1-26) were distributed on 14 poplar chromosomes either individually or in groups of two to four. PtMLO genes encoded a polypeptide of 341-593 residues with a characteristic MLO domain structure. One tandem and eight segmental duplications were revealed in PtMLO genes. PtMLO proteins anchored at plasma membrane and had putative 5-9 TMDs with extracellular/cytosolic N- and C-terminuses. They were rich in leucine (9.1-12.9%), which is reported to play roles in defense response signaling. The C-terminal calmodulin-binding domain (CaMBD), reported to modulate the signaling mechanism in the defense response, was completely preserved in all PtMLOs, except PtMLO6. This domain was partially absent in PtMLO6 which is inferred to be a different MLO type or a pseudogene with a lost/impaired function in PM response. Besides, second and third cytoplasmic loops that are critical for PM-susceptibility were identified in PtMLOs. Particularly, PtMLO17, 18, 19, and 24 genes, inferred from Arabidopsis-poplar comparative phylogeny, were identified as potential candidates that may be involved in poplar-PM resistance. Notably, inductions of 14 PtMLO genes were detected in probes of microarray data such as GSE56865, GSE16417, and GSE23726 under different fungal infections indicating their involvements in plant defense. Overall, this work provided a basis for woody plant genomics for the effective and better management of poplar-PM disease.
Keywords: Poplar; Powdery mildew; MLO; Susceptibility gene; Fungal disease; CALMODULIN-BINDING PROTEIN; CELL-DEATH; EXPRESSION OMNIBUS; FAMILY-MEMBERS; GLYCINE-MAX; PREDICTION; DEFENSE; HYBRIDIZATION; MODULATOR; TOPOLOGY